The enhancement of gene silencing efficiency with chitosan-coated liposome formulations of siRNAs targeting HIF-1 alpha and VEGF - EREN, FATİH; ÖZBAŞ, SUNA (ELSEVIER SCIENCE BV, 2015)
RNA interference (RNAi) holds considerable promise as a novel therapeutic strategy in the silencing of disease-causing genes. The development of effective delivery systems is important for the use of small interfering RNA (siRNA) as therapy. In the present study, we investigated the effect on breast cancer cell lines and the co-delivery of liposomes containing siHIF1-alpha and siVEGF. In order to achieve the co-delivery of siHIF1-alpha and siVEGF and to obtain lower cytotoxicity, higher transfection and silencing efficiency, in this study, we used chitosan-coated liposomal formulation as the siRNA delivery system. The obtained particle size and zeta potential values show that the chitosan coating process is an effective parameter for particle size and the zeta potential of liposomes. The liposome formulations loaded with siHIF1-alpha and siVEGF showed good stability and protected siRNA from serum degradation after 24-h of incubation. The expression level of VEGF mRNA was markedly suppressed in MCF-7 and MDA-MB435 cells transfected with chitosan-coated liposomes containing siHIF1-alpha and VEGF siRNA, respectively (95% and 94%). In vitro co-delivery of siVEGF and siHIF1-alpha using chitosan-coated liposome significantly inhibited VEGF (89%) and the HIF1-alpha (62%) protein expression when compared to other liposome formulations in the MDA-MB435 cell. The co-delivery of siVEGF and siHIF1-alpha was greatly enhanced in the vitro gene silencing efficiency. In addition, chitosan-coated liposomes showed 96% cell viability. Considering the role of VEGF and HIF1-alpha in breast cancer, siRNA-based therapies with chitosan coated liposomes may have some promises in cancer therapy. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: siRNA; Chitosan; Liposome; VEGF; HIF-1 alpha; Breast cancer; INDUCIBLE FACTOR-I; CANCER CELL-LINE; BREAST-CANCER; NORMOXIC CONDITIONS; CATIONIC LIPOSOMES; CO-DELIVERY; HYPOXIA; GROWTH; EXPRESSION; HIF-1